2007
DOI: 10.3892/or.17.3.549
|View full text |Cite
|
Sign up to set email alerts
|

SIAH1 causes growth arrest and apoptosis in hepatoma cells through β-catenin degradation-dependent and -independent mechanisms

Abstract: Abstract.We have previously shown that expression of SIAH1 is frequently down-regulated in HCCs and associated with their advanced stages. It has been shown that SIAH1 functions in the phosphorylation-independent degradation of ß-catenin and induces apoptosis and growth arrest. To examine if the effects of SIAH1 overexpression depend on the altered ß-catenin signaling pathway, we transferred the SIAH1 gene into three hepatoma cell lines with different genetic backgrounds: HepG2 (mutant ß-catenin), SNU475 (muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 17 publications
(25 reference statements)
1
40
0
Order By: Relevance
“…In other cancers, such as gastric and liver cancer, low levels of Siah1 have been shown to reduce apoptosis, thereby promoting cancer progression (25,26). Together these studies and those listed in Table 1 allude to a tumor-suppressive role for Siah1 proteins in various cancer types.…”
Section: Tumor-suppressor Rolementioning
confidence: 80%
“…In other cancers, such as gastric and liver cancer, low levels of Siah1 have been shown to reduce apoptosis, thereby promoting cancer progression (25,26). Together these studies and those listed in Table 1 allude to a tumor-suppressive role for Siah1 proteins in various cancer types.…”
Section: Tumor-suppressor Rolementioning
confidence: 80%
“…Moreover, following the spinal cord injury, the coexpression of SIAH1 and active caspase-3 were detected in our study. Previous studies have shown that enhanced expression of SIAH1 appeared to be linked with apoptotic signal (Yoshibayashi et al 2007;Wen et al 2010a,b). Overexpression of SIAH1 can induce apoptosis of neuronally differentiated PC12 cells in vitro (Xu et al 2006).…”
Section: Discussionmentioning
confidence: 93%
“…To date, several important targets of the SIAH1-dependent ubiquitin-proteasome pathway have been identified (Venables et al 2004;Hara et al 2005;Santelli et al 2005;Zhou et al 2008;Kim et al 2009). Increased expression of SIAH1 is observed to be associated with the onset of nontumorigenicy in revertant tumorigenic cell lines and with several apoptotic processes (Matsuo et al 2003;Okabe et al 2003;Yoshibayashi et al 2007;Wen et al 2010a,b). Besides, some reports showed that SIAH1 can trigger activation of the c-Jun NH2-kinase (JNK) signaling pathway (Xu et al 2006;Wen et al 2010a,b).…”
Section: Introductionmentioning
confidence: 92%
“…The reduced mRNA expression of SIAH1 was first reported to be significantly related with advanced HCCs, including the larger, poorly differentiated tumors, and the tumors in advanced stages [63]. SIAH1 causes growth arrest and apoptosis in HCC cells through β-catenin degradation-dependent and -independent mechanisms [64] or facilitating the p53-mediated HBx degradation [65]. After that, Malz and his colleagues found a reduction of cytoplasmic SIAH1 but an accumulation of nuclear SIAH1 in HCC tissues.…”
Section: The Ubiquitin Enzymementioning
confidence: 95%